2019
DOI: 10.1126/sciadv.aax5078
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of fossil asteroidal ice in primitive meteorite Acfer 094

Abstract: Discovery of fossil asteroidal ice in a meteorite provides new insight into asteroid formation in the early Solar System.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…S1). The samples were imaged using SR-XCT to obtain their three-dimensional (3D) images with absorption and phase-shift contrasts using two different methods: dual-energy tomography (DET) ( 7 ) and scanning-imaging x-ray microtomography (SIXM) ( 8 ) with ~70 and 100 nm in voxel size, respectively ( 3 ). A large number of inclusions in the interior of calcite grains were recognized in 3D ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1). The samples were imaged using SR-XCT to obtain their three-dimensional (3D) images with absorption and phase-shift contrasts using two different methods: dual-energy tomography (DET) ( 7 ) and scanning-imaging x-ray microtomography (SIXM) ( 8 ) with ~70 and 100 nm in voxel size, respectively ( 3 ). A large number of inclusions in the interior of calcite grains were recognized in 3D ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the LAC and RID values obtained by the reconstruction are slightly smaller than the real values, we corrected the LAC and RID values by calibration using standard materials as performed in ( 3 ). We searched for inclusions in the CT images by both DET and SIXM, and their locations in the samples in 3D were recognized using an open source image processing package “Fiji-ImageJ.” Inclusions in calcite grains were digitally extracted by binarization of 3D-CT images, and their bird’s-eye views were made ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous alteration in CM chondrites was driven by mild heating that caused melting of water ice physically intermixed with silicate matter. The former presence of water ice has long been inferred by many studies of CM chondrites and was recently convincingly demonstrated by Matsumoto et al (2019). Such CMs are commonly referred to as aqueously altered.…”
Section: Introduction Background and Statement Of Problemmentioning
confidence: 86%
“…In this context, it is necessary to perform multiple complementary analyses on micrometer-sized samples, from the least destructive to the most destructive methods to maximize scientific outcomes and minimize sample loss and contamination. Multi-analytical sequences were successfully used in the recent past to analyze (1) samples from comet Wild 2 and asteroid Itokawa returned by the Stardust and Hayabusa space missions, respectively (e.g., Zolensky et al 2008;Nakamura et al 2011); and (2) very small and unique meteorites (e.g., Acfer 094, Matsumoto et al 2019). Those sequences either consisted of successive analyses on the same thin section such as XANES (X-ray absorption near edge structure), TEM, and finally NanoSIMS which, in the end, consumed integrally the section (e.g., Stadermann et al 2005;Zolensky et al 2008;De Gregorio et al 2011), or consisted of 3-D-XCT (X-ray computed tomography), -XRD (X-ray diffraction), or -XRF (X-ray fluorescence) analyses of a grain subsequently sliced in several sections, which were analyzed independently by different techniques (e.g., TEM or NanoSIMS, Nakamura et al 2011;Matsumoto et al 2019).…”
Section: Introductionmentioning
confidence: 99%